Effect of Codigestion of Rice Straw, Fish Meal, and Cow Manure on Biogas Production and Quality of Solid Bioslurry Fertilizer - Sri Ismiyati Damayanti; Rifki Amirul Hakim; Anggi Anggraeni; Yuni Saputri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The solid phase bioslurry (sludge) had the potential to be used as organic fertilizer. However, the NPK content in it did not meet SNI standards. This research aimed to study the effect of adding rice straw and fish meal to cow dung substrate for anaerobic processing, on the NPK content of the sludge produced and biogas production. Two digesters were used, which functioned as a control and a codigestion digester. Initially, in both digesters, starter breeding was carried out in batches. After the starter had grew well, then the substrate along with water was fed continuously at 88 mL/day in each digester, and an output of 88 mL/day was also produced. Analysis of COD, sCOD, VFA concentrations, and measurements of the pH values of feed and output were carried out every 3 days. Biogas volume measurements were carried out every day. The process was stopped when conditions were steady. At the end of the process, an analysis of the NPK content in the sludge and the methane content in the biogas were carried out. The results showed that biogas from codigestion content almost no methane. However, the sludge contained NPK within the range of SNI standard. Keywords: Biogas, Cow dung, Fish meal, Rice straw, Solid bioslurry fertilizer.